Exposure to aflatoxins greater among poor in eastern Kenya - Leroy, Jef L.; Wang, Jia-Sheng; Jones, Kelly M. (International Food Policy Research Institute, 2015)
This study is the first to show the significant association between poverty and aflatoxin exposure. Yet, whether or not aflatoxin truly causes child stunting is a question that can only be answered through a rigorous approach, such as a randomized-controlled trial. In the meantime, knowing that the poorest families are at the greatest health risk from this food-borne toxin suggests that ad-dressing aflatoxin contamination should be a priority for policy-makers concerned about the welfare of the poor. Furthermore, a better understanding of how better-off families manage to miti-gate aflatoxin exposure can be used to develop strategies that pro-tect the poor.